1997
DOI: 10.1128/aem.63.5.1712-1714.1997
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of glyceryl trinitrate by Penicillium corylophilum Dierckx

Abstract: Penicillium corylophilum Dierckx, isolated from a contaminated water wet, double-base propellant, was able to completely degrade glyceryl trinitrate (GTN) in a buffered medium (pH 7.0) containing glucose and ammonium nitrate. In the presence of 12 mg of initial fungal inoculum, GTN (48.5 to 61.6 mol) was quantitatively transformed in a stepwise process to glyceryl dinitrate (GDN) and glyceryl mononitrate (GMN) within 48 h followed by a decrease in the GDN content with a concomitant increase in the GMN level. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These authors suggested that NG was denitrated hydrolyti cally to form nitrate, which was subsequently reduced to nitrite by nitrate reductase. Reductive biotransformation of NG to its reduction products and nitrite by mixed culture, pure bacteria, and fungi was also reported ( ). Christodoulatos and co-workers ( , ) reported that NG was transformed cometabolically to DNGs and MNGs under both aerobic and anaerobic conditions, with concomitant release of nitrite and nitrate.…”
Section: Introductionmentioning
confidence: 95%
“…These authors suggested that NG was denitrated hydrolyti cally to form nitrate, which was subsequently reduced to nitrite by nitrate reductase. Reductive biotransformation of NG to its reduction products and nitrite by mixed culture, pure bacteria, and fungi was also reported ( ). Christodoulatos and co-workers ( , ) reported that NG was transformed cometabolically to DNGs and MNGs under both aerobic and anaerobic conditions, with concomitant release of nitrite and nitrate.…”
Section: Introductionmentioning
confidence: 95%
“…In the case of the present mixed culture, results from the shake‐flask experiments indicate that the accumulation of DNGs is transient and that denitration can eventually proceed to completion. However, other cultures are known to achieve denitration only until the DNG stage (Ducrocq et al, 1989; White and Snape, 1993; Zhang et al, 1997; Marshall and White, 2001), which could lead to the accumulation of these products in groundwater. Because of the possibility of accumulation and considering the lack of data concerning their toxicity to mammals, the possible presence of DNGs in groundwater as a result of NG biodegradation is of concern.…”
Section: Resultsmentioning
confidence: 99%
“…These processes have been sparsely documented for NG, but for other explosives, such as 2,4,6‐trinitrotoluene (TNT) and hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX), biodegradation has been considered as the main naturally occurring degradation process (Pennington et al, 2001; Bernstein et al, 2010). Biodegradation could also be important for NG, according to results from laboratory experiments conducted with moist soils (Jenkins et al, 2003; Clausen et al, 2011) or in shake flasks with various microorganisms (Meng et al, 1995; White et al, 1996; Zhang et al, 1997; Accashian et al, 1998; Marshall and White, 2001; Husserl et al, 2010; Husserl et al, 2012). Most NG biodegradation studies have been conducted in the perspective of developing active remediation strategies for contaminated wastewater.…”
mentioning
confidence: 99%